Ruang Sempit Petani Puger Pasca Industrialisasi - Estu Ningrum, Siti Rahayu; Nur Widyatama, Arif; Sri Utami, Rofi (Jurnal Sosiologi Pertanian dan Agribisnis, 2023)
Contains Puger Village is one of the villages that has quite good agricultural commodities and has a large area of land. However, there is a problem where farmers feel disadvantaged and even cheated by the factory. This study aims to describe and examine the space for farmers to move after the construction of the Imasco Asiatic cement factory. This study used a descriptive qualitative method using an ethnographic approach, and is located in Puger Kulon Village, Puger District, Jember Regency, East Java Province. While the informants in this study were seven farmers affected by industrialization. Collecting data through interviews, observation, and documentation. The results of the study show that farmers are still forced to work in the agricultural sector because apart from being limited by their educational status, they have also developed the agricultural sector from generation to generation.